2009
DOI: 10.1007/s11999-009-0773-2
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic-Ceramic Bearing Decreases Osteolysis: A 20-year Study versus Ceramic-Polyethylene on the Contralateral Hip

Abstract: Although ceramic implants have been in use for many years and they are intended to minimize wear debris it is unknown whether alumina-on-alumina or alumina-onpolyethylene produce less wear and osteolysis. We therefore investigated wear and osteolysis on 28 bilateral arthroplasties (one ceramic-ceramic and the contralateral ceramic-polyethylene) of patients who had survived 20 years without revision and without loosening of either hip. Osteolysis was identified on anteroposterior pelvic radiographs and 3-D volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 28 publications
2
37
0
4
Order By: Relevance
“…However, our findings suggest that patients should be informed of this problem when a THA with alumina-on-alumina bearings is considered. Previous studies report an incidence of osteolytic lesions ranging from 0% to 46% at 10 to 22 years after THAs using alumina-on-alumina bearings [3,18,24,29]. According to a 10-year followup study by Kim et al [21], no osteolysis was observed in 93 hips of patients operated on when the patients were younger than 45 years, and this result was supported by CT scans.…”
Section: Discussionmentioning
confidence: 80%
“…However, our findings suggest that patients should be informed of this problem when a THA with alumina-on-alumina bearings is considered. Previous studies report an incidence of osteolytic lesions ranging from 0% to 46% at 10 to 22 years after THAs using alumina-on-alumina bearings [3,18,24,29]. According to a 10-year followup study by Kim et al [21], no osteolysis was observed in 93 hips of patients operated on when the patients were younger than 45 years, and this result was supported by CT scans.…”
Section: Discussionmentioning
confidence: 80%
“…Osteolytic lesions around femoral component worsen over time [10], although the rate is highly variable. Patients with a THA that requires cup revision for loosening or osteolysis may have a stable stem component without loosening.…”
Section: Introductionmentioning
confidence: 99%
“…In radiographic assessment of hip arthroplasty, 2 mm is commonly used as a critical measurement of width of radiolucency [29]. Numerous authors consider linear radiolucencies greater than 2 mm a definite indication of loosening of the prosthesis [6,8,17,34]. Therefore, a grid was developed and printed on transparency film with 2 mm between each point, which was a small cross at the intersection of grid lines.…”
Section: Methodsmentioning
confidence: 99%
“…This requires more precise measurement to quantify progressive changes. The area of a lesion has been measured in numerous ways, including geometric formulae and computer software [15,17,31], but these techniques are not readily applied in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation